2012
DOI: 10.1093/jac/dks351
|View full text |Cite
|
Sign up to set email alerts
|

TetAB(46), a predicted heterodimeric ABC transporter conferring tetracycline resistance in Streptococcus australis isolated from the oral cavity

Abstract: ObjectivesTo identify the genes responsible for tetracycline resistance in a strain of Streptococcus australis isolated from pooled saliva from healthy volunteers in France. S. australis is a viridans Streptococcus, originally isolated from the oral cavity of children in Australia, and subsequently reported in the lungs of cystic fibrosis patients and as a cause of invasive disease in an elderly patient.MethodsAgar containing 2 mg/L tetracycline was used for the isolation of tetracycline-resistant organisms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Several bacterial species were more abundant in the gut microbiota of CP patients compared to those of AIP patients. Among them, Streptococcus australis and Streptococcus gordonii are generally present in the oral cavity, sometimes causing bacterial endocarditis (Warburton et al 2013;Dadon et al 2017). A greater abundance of Streptococcus has also been found in patients with intestinal diseases in a meta-analysis (Mancabelli et al 2017), suggesting a possible contribution of these bacterial species during the dysbiosis of CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several bacterial species were more abundant in the gut microbiota of CP patients compared to those of AIP patients. Among them, Streptococcus australis and Streptococcus gordonii are generally present in the oral cavity, sometimes causing bacterial endocarditis (Warburton et al 2013;Dadon et al 2017). A greater abundance of Streptococcus has also been found in patients with intestinal diseases in a meta-analysis (Mancabelli et al 2017), suggesting a possible contribution of these bacterial species during the dysbiosis of CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Each PCR product was gel purified, and 100 ng of each fragment was fused by using PCR, as described previously (51). PCR products were excised from an agarose gel, purified, and used to transform A12 by using a modification of a method originally developed for Streptococcus australis (52). Briefly, a single colony was inoculated into Todd-Hewitt broth (THB) containing 10% heat-inactivated horse serum and incubated for 16 to 18 h. Cells were diluted 1:40 into THB supplemented with 10% horse serum and incubated until the optical density at 600 nm (OD 600 ) reached 0.05 to 0.08.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated links between ABC transporter proteins and drug resistance. For example, the enterococcal ABC transporter gene lsa(E) conferred resistance to lincosamides in Staphylococcus aureus (42), and a predicted heterodimeric ABC transporter, TetAB, conferred tetracycline resistance in Streptococcus australis (43). Moreover, ABC transporters together with neighboring two-component systems, which regulate their expression, could coevolve to form self-sufficient detoxification modules against antimicrobial peptides in Firmicutes bacteria (44).…”
Section: Discussionmentioning
confidence: 99%